The Determination of the Boron Amounts of Teas That Are Sold In Turkey by Using the ICP-OES Technique - Derun, E. Moroydor; Kipcak, A. S.; Ozdemir, O. Dere (INT ASSOC ENGINEERS-IAENG, 2010)
Tea refers to the agricultural products of the leaves, leaf buds, and internodes of Camellia sinensis, prepared and cured by various methods. Tea also refers to the aromatic beverage prepared from such cured leaves by combination with hot or boiling water and is the colloquial name for the Camellia sinensis plant itself. Tea is the most widely-consumed beverage after water. It has a cooling, slightly bitter, astringent flavor. The four types of tea most commonly found on the market (in descending order of oxidation) are black tea, oolong tea, green tea and white tea, all of which can be made from the same bushes, processed differently, and in the case of fine white tea, grown differently. In Turkey, mostly tea is produced in the region of Eastern Black Sea. The important tea producers in the world are: India, Sri Lanca, China, Turkey, Kenya, Indonesia, Malawi and Vietnam. In this study the teas selected are: black tea, camomile tea, apple tea, rosehip tea, sage tea, linden tea and green tea, which are produced by Lipton. Optical emission spectroscopy (ICP-OES) was used to determine the boron amount that is introduced to the human body while drinking, by the method of brewing the teas. These teas were brewed with 90-100 degrees C hot water for 5 minutes and the obtained filtrates' boron concentrations were determined by Inductively Coupled Plasma-Optical Emission Spectroscopy technique. The boron content in the tea results of the experiments vary between the values of 0.084 and 2.023 ppm.
Keywords: Boron; tea; ICP-OES; hot water brewing; Engineering